Contesting Mexico City's alleged polycentric condition through a centrality-mixed land-use composite index - Escamilla, Jorge Montejano; Cos, Camilo Caudillo; Cárdenas, José Silván (Urban studies (Edinburgh, Scotland), 2016)
We examine Mexico City's urban structure through a composite index by combining two previously existing metrics: one derived from the Urban Network Analysis tool (UNA), recently published by MIT researchers, and the other, using an Entropy Index, which in essence, represents the mixed land-use degree. The proposed composite index embodies a different approach from previous methods reported in the literature because it uses disaggregated data at the unit level, performs weighted cluster calculations through a network data set, and incorporates a mixed land-use metric. This method was developed in order to test if the urban arrangement showed signs of a polycentric condition under a particular centrality standpoint. We observed that Mexico City has a relatively weak polycentric urban condition.